Two-Step Optimization Model for Evaluating the Saturation Flow Rate under the Impact of Small-Sized Vehicles - Mondal S.; Gupta A.; Zhao J. (My University, 2025)
Saturation flow rate (SFR) is a vital input for an intersection's performance evaluation and development of signal control strategy. Several models have been framed under prevailing traffic conditions for homogeneous and for mixed traffic scenarios. However, studies of mixed traffic streams focus on regulated traffic, mainly observed in metropolitan cities. Midsized cities have different demands, driver characteristics, and intersection properties due to the substantial percentage of small vehicles (especially motorized two- and three-wheelers) in the traffic stream. Thus, there is a need for different policy and planning initiatives than in metropolitan cities. This study framed a two-step optimization model (TSOM) for evaluating the SFR at signalized intersections considering the traffic situations in midsized cities. Thirteen intersections from four different midsized cities in India were used to analyze and model SFR. A saturation flow prediction model (SFPM) was developed using various traffic properties. The superiority of the SFPM was checked by comparing the result with those of other developed models proposed in the literature and the Indian design guide. The results showed significantly better performance of the SFPM than of the existing models. Thus, this study illustrates the effectiveness of the proposed methodology for SFR evaluation in complex traffic situations for midsized cities with a higher percentage of small vehicles. © 2022 American Society of Civil Engineers.